Free radical scavenging and antibacterial activities of Malaysian guttiferae plants - Darnis, Deny Susanti; Bakhtiar, M. Taher; Nissad, Attoumani; Ahmad, Farediah (Academic Journals, 2011)
Guttiferae family is well known to have wide range of biological activities. The family is distributed throughout Malaysia, especially the genus of Calophyllum and Garcinia. Some of the species shows interesting bioactivity, such as Calophyllum lanigerum found in Borneo is exhibited anti- human immunodeficiency virus (HIV) properties. The study was conducted to determine the antioxidant and antibacterial activities of the extracts of selected Guttiferae collected in Malaysia. About 23 extract from different part of nine plants namely Calophyllum canum, Calophyllum depressinervosum, Calophyllum macrocarpum, Calophyllum teysmanii, Calophyllum symingtonianum, Garcinia griffithii, Garcinia prainiana, Garcinia malaccensis and Mesua grandis were tested for their free radical scavenging and antibacterial activities. Free radical scavenging activity was screened using dot blots 1, 1 -diphenyl-2-picrylhydrazyl (DPPH) staining and followed by DPPH free radical reaction. The antibacterial activity of these plant extracts was tested in vitro by using disc diffusion method and minimum inhibitory concentration (MIC). n-Hexane extract of the stem bark of G. griffithii showed higher scavenging activity with an IC50 of 0.09 mg/ml followed by n-hexane extract of the leaves of G. griffithii with an IC50 of 0.098 mg/ml. The antibacterial activity of the extracts revealed that the n-hexane extract of the stem bark of C. canum, C. teysmanii and M. grandis have the highest antibacterial effect with same MIC value at 0.25 mg/ml on the Bacillus cereus.